2008
DOI: 10.1164/rccm.200703-381oc
|View full text |Cite
|
Sign up to set email alerts
|

Continued Exposure to Maternal Distress in Early Life Is Associated with an Increased Risk of Childhood Asthma

Abstract: Maternal distress in early life plays a role in the development of childhood asthma, especially if it continues beyond the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 37 publications
9
158
0
3
Order By: Relevance
“…This study found a highly significant effect of behavioural difficulties preceding the onset of parent-reported wheeze (OR 8.95). KOZYRSKYJ et al [17] used medical records to investigate the link between maternal depression and/or anxiety diagnosis and physician diagnosis of asthma in their children. At 7-year follow-up, the authors report a mildly significant effect (OR 1.25) with subsequent analyses revealing a dose-response relationship between intensity and severity of mental health difficulties and likelihood of asthma diagnosis.…”
Section: Parental Mental Health Difficulties and Asthma Onsetmentioning
confidence: 99%
“…This study found a highly significant effect of behavioural difficulties preceding the onset of parent-reported wheeze (OR 8.95). KOZYRSKYJ et al [17] used medical records to investigate the link between maternal depression and/or anxiety diagnosis and physician diagnosis of asthma in their children. At 7-year follow-up, the authors report a mildly significant effect (OR 1.25) with subsequent analyses revealing a dose-response relationship between intensity and severity of mental health difficulties and likelihood of asthma diagnosis.…”
Section: Parental Mental Health Difficulties and Asthma Onsetmentioning
confidence: 99%
“…Maternal distress in early life may play a role in the development of childhood asthma, especially if the distress continues beyond the postpartum period 43 .…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Atopic asthma 3 20 n/a 23 n/a n/a n/a 23 Caucasian (79.2%); (2) the Study of Asthma Genes and Environment (SAGE) cohort (Kozyrskyj et al 2008;Mai et al 2007) composed of 723 children and their parents from Manitoba, Canada, who are primarily Caucasian (74.2%); (3) the Saguenay-Lac-Saint-Jean and Quebec City Familial Asthma Collection (SLSJ) (Begin et al 2007;Laitinen et al 2004;Laprise et al 2004;Poon et al 2004Poon et al , 2005Raby et al 2002;Tremblay et al 2006) consisting of a French-Canadian founder population panel of 306 multigenerational families with at least one asthmatic proband; and (4) The Busselton Health Study (Busselton) (James et al 2005a, b), a population-based, nested, case-control panel of 1,549 individuals of European Caucasian descent from Australia. Of note is that at the time of phenotyping, subjects in the CAPPS and SAGE panels were between the ages of 6 and 8 (birth cohorts), whereas subjects in the SLSJ and Busselton panels were primarily teenagers or adults.…”
Section: Study Samples (Panels)mentioning
confidence: 99%